Anesthetic management in a spinal cord-injured parturient woman with a left hip resection and secondary scoliosis: A case report. Issue 8 (February 2019) - Liu, Hui; Lin, Xuemei; Diao, Min; Ma, Yushan
Abstract: Rationale: Pregnancy after spinal cord injury, hip resection, leg amputation, and scoliosis is an uncommon event. Given the specific pathophysiological changes in this patient, an aesthetic management presented a particular challenge. The effects on the physiological changes associated with pregnancy, aesthetic methods, blood loss, autotransfusion from uterine contractions and thrombotic risk had to be considered. Patient concerns: A 25-year-old female earthquake survivor was admitted at 36.4 weeks of pregnancy for preterm labor. She had suffered from a spinal cord injury and complex trauma and had subsequently undergone left hip resection, bilateral amputations, and multiple surgical procedures during the previous 6 years. Additionally, she had developed severe scoliosis due to her weight-bearing posture. Diagnoses: High amputation after earthquake injury; Scoliosis; Vulvar reconstruction; Intrauterine pregnancy (35.6 weeks) with a single live fetus with possible premature delivery. Interventions: We administered general anesthesia during a cesarean section for the parturient woman. Both the central venous pressure and pleth variability index were used to continuously evaluate intraoperative fluid management and blood loss. Outcomes: Delivery and patient recovery were uneventful. Lessons: Anesthetic management of a pregnant woman with a spinal injury, scoliosis, left total leg and right below-knee amputations, and left hip resection requires considerable attention. Advances in medical technology have provided clinicians with insights into managing patients with this condition.